Forster's tern chick survival in response to a managed relocation of predatory California gulls. Issue 5 (18th June 2014) - Ackerman, Joshua T.; Herzog, Mark P.; Hartman, C. Alex; Herring, Garth
ABSTRACT Gull populations can severely limit the productivity of waterbirds. Relocating gull colonies may reduce their effects on nearby breeding waterbirds, but there are few examples of this management strategy. We examined gull predation and survival of Forster's tern (Sterna forsteri) chicks before (2010) and after (2011) the managed relocation of the largest California gull (Larus californicus) colony (24, 000 adults) in San Francisco Bay, California. Overall, survival of radio‐marked Forster's tern chicks from hatching to fledging was 0.22 ± 0.03 (mean ± SE), and daily survival rates increased with age. Gulls were the predominant predator of tern chicks, potentially causing 54% of chick deaths. Prior to the gull colony relocation, 56% of radio‐marked and 20% of banded tern chicks from the nearest tern colony were recovered dead in the gull colony, compared to only 15% of radio‐marked and 4% of banded chicks recovered dead from all other tern colonies. The managed relocation of the gull colony substantially increased tern chick survival (by 900%) in the nearby (<1 km) colony from 0.04 ± 0.02 in 2010 to 0.40 ± 0.12 in 2011 but not at the more distant (>3.8 km) reference tern colony (0.29 ± 0.10 in 2010 and 0.25 ± 0.09 in 2011). Among 19 tern nesting islands, fledging success was higher when gull abundance was lower at nearby colonies and when gull colonies were farther from the tern colony. Our results indicate that the managed relocation of gull colonies away from preferred nesting areas of sensitive waterbirds can improve local reproductive success, but this conservation strategy may shift gull predation pressure to other areas or species. © 2014. This article is a U.S. Government work and is in the public domain in the USA.